On-Surface Atomic Wires and Logic Gates : Updated in 2016 Proceedings of the International Workshop on Atomic Wires, Krakow, September 2014 - Kolmer, Marek; Joachim, Christian (Springer International Publishing : Imprint: Springer, 2017)
Written by leading international experts, this book summarizes the advances in sample preparation, design and construction of dangling bond atomic scale wires and logic gate circuits at the surface of a passivated semi-conductor. Individual chapters cover different aspects of the sample fabrication from research and development point of view, present design and construction as well as microscopic and spectroscopic characteristics of single dangling atomic wires and logic gates, and discuss the tools for design of large atomic scale circuit on a surface. This edited volume includes selected contributions from the "International Workshop on Atomic Wires" held in Krakow in September 2014 completed and updated with most current results up to mid-2016, and offers for the first time an overview of up-to-date knowledge in the burgeoning field of atomic scale circuits. The book will appeal to researchers and scholars interested in nanoscience and its various sub-fields including, in particular, molecular electronics, atomic scale electronics and nanoelectronics.
Keywords: Chemistry.; Nanochemistry.; Surfaces (Physics).; Interfaces (Physical sciences).; Thin films.; Optical materials.; Electronic materials.; Materials -- Surfaces.; elektronické knihy; electronic books